PEMANFAATAN BUAH EDIBEL OLEH SUKU DAYAK BAKATI DI HUTAN TEMBAWANG DESA TIRTA KENCANA KECAMATAN BENGKAYANG KABUPATEN BENGKAYANG - Wibowo, Anggi; Rafdinal, Rafdinal; Ifadatin, Siti (Universitas Tanjungpura, 2019)
The Dayaknese people of Bakati in Tirta Kencana Village at Bengkayang District of Bengkayang Regency have a Tembawang forest that planted with edibel forest fruits. This study aims to determine the types of edible fruits that have been consumed by residents of Tirta Kencana Village at Bengkayang District of Bengkayang Regency. This research has been carried out for two months from April 2019 to May 2019. This research was used a survey and interview methods. Edibel fruit found in the Tembawang forest that consists of 21 which belong to 14 families. The part of the fruit that is eaten in the flesh of the seed coat. The use of edible fruit by the local population is still relatively simple, which is either eaten directly, cooked, processed by fermentation, processed into candied snacks and cooking spices.